2020
DOI: 10.1017/s1368980019003689
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Chinese consumers’ knowledge, beliefs and behavioural intentions regarding salt intake and salt reduction

Abstract: Objective:Globally, China is among the ‘saltiest’ nations. In order to support current nationwide salt reduction initiatives, we investigated Chinese consumers’ knowledge, beliefs and behaviours related to salt intake and salt reduction.Design:A cross-sectional face-to-face survey was carried out, focusing on salt knowledge, beliefs and behaviours related to salt intake and salt reduction, perceptions of salt reduction responsibility and support for different national strategies.Setting:The survey was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 25 publications
(46 reference statements)
5
31
0
1
Order By: Relevance
“…In most families of China, female are responsible for cooking, and they care about the healthy diet of family members, which may lead to more attention to salt-related knowledge. It was reported that better-educated people, females and young people were more knowledgeable about salt-reduction tips [33]; a similar result was found in this study, and the salt-related knowledge of the 45-years-old-and-below group was higher than those in over-45-years-old group. It should be noted that low salt-related knowledge, salt reduction score and highsalt intake behavior score were found in the hypertension patients group in this study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In most families of China, female are responsible for cooking, and they care about the healthy diet of family members, which may lead to more attention to salt-related knowledge. It was reported that better-educated people, females and young people were more knowledgeable about salt-reduction tips [33]; a similar result was found in this study, and the salt-related knowledge of the 45-years-old-and-below group was higher than those in over-45-years-old group. It should be noted that low salt-related knowledge, salt reduction score and highsalt intake behavior score were found in the hypertension patients group in this study.…”
Section: Discussionsupporting
confidence: 89%
“…This study found that the percentage of WeChat users who had the willingness of reducing the amount of cooking salt in their households was quite high between 2019 and 2020 in China, but the awareness level of salt-related knowledge varied greatly, similar to the result of a survey of 2444 Chinese consumers in 2017 [33]. Over 60% of participants knew all four provided condiments contain salt and should be used less or three types of diseases related to excessive salt intake, but lower than 25% of participants knew all the five foods listed contain salt in this study.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations